Fertility preservation methods for female neoplastic patients - Del Pup, Lino (Radiology and oncology (Ljubljana), 2006)
Background. The ability to have biological children is of great importance to cancer patients and fertility preservation before the oncological treatment isnowadays not rare. Oncologists have the responsibility to inform patients about the risks that their cancer treatment will permanently impair fertility and about the ways to limit this iatrogenic damage. Methods of fertility preservation are evolving quickly, yet the medical oncology literature is still poor regarding this topic. Indications and contraindications, limits andcontroversies of the fertility sparing techniques are reviewed in order to help the oncologist to counsel patients. Conclusions. Any oncologist seeing reproductive-aged patients should discuss the fertility implications of the oncological treatment and the fertility preservation options. A referral to appropriate fertility specialists as early as possible is recommended. People attempting fertility preservation in the context of cancer treatment are encouraged to enrol in clinical trials.
Keywords: Cryopreservation; Embrio; Embryo; Fertility; Fertilization In Vitro; in vitro fertilization; Jajčne celice; Jajčnik; Krioshranjevanje; Neoplasms; Novotvorbe; onkologija; Oocytes; Oploditev in vitro; Ovary; Plodnost; rak (medicina); tumor; zaščita